Percursos da cartografia ao jogo: reflexões acerca do processo criativo - Geron Junior, Clóvis [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The creative processes are always arduous, mysterious and involving, taking those involved in them through unknown paths. The goal proposed here is to make a series of reflections about creativity. To help the process, I make my own cartography in the creation of games during the undergraduation period, creating a system where the geographic coordinates are creativity and games. A practical-theoretical experience so that I am able to analyze my own process. To support the arguments exposed in this experiment, various concepts about cartography, creativity and games by different authors will be presented, from an anthropological perspective, to the perspective of authors related to creation, going through treatments situated in the art of theater.

Os processos criativos são sempre árduos, misteriosos e envolventes, levando aqueles que com ele se envolvem a caminhos desconhecidos. O objetivo proposto aqui é fazer uma série de reflexões acerca da criatividade. Para auxiliar o processo, faço minha própria cartografia na criação de jogos durante o período da graduação, criando um sistema onde as coordenadas geográficas são a criatividade e os jogos. Uma experiência prático-teórica para que eu possa analisar meu próprio processo. Para apoiar os argumentos expostos nesta experimentação, serão apresentados conceitos sobre cartografia, criatividade e jogos, pensados por autores diferentes, desde um viés antropológico, até a perspectiva de autores e autoras relacionados à criação, passando por tratamentos situados na arte do teatro.
Paths from Cartography to the Game: reflections on the creative process
Keywords: Jogo; Criação; Cartografia; Criatividade